A high-impact PC- elastomer composite battery case and method of making the same

CN121939053BActive Publication Date: 2026-10-23GUANGDONG SEONLON NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610134651.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-01-30
Publication Date
2026-10-23
Estimated Expiration
2046-01-30

AI Technical Summary

Technical Problem

传统金属壳体较重且在某些腐蚀性环境中易发生化学反应,影响其使用寿命

Benefits of technology

(1)本发明通过三层结构协同提升电池壳体的抗冲击性能,其中外层以PC作为初始冲击分散;再通过中间层吸收冲击能量,中间层双交联网络包含聚氨酯硬段和呋喃-聚己内酯二醇与双马来酰亚胺的交联结构,冲击时,聚氨酯硬段提供了基本的机械强度和韧性,同时Diels-Alder反应通过链段滑移耗散冲击能,进一步提升抗冲击性能;内层通过添加改性玻璃纤维为电池壳体提供刚性骨架,抵抗冲击时的局部形变。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to a high-impact PC-elastic body composite battery shell and a preparation method thereof, and belongs to the technical field of battery shell manufacturing. The shell adopts a three-layer composite structure design, comprises an outer layer polycarbonate layer grafted with a terminal base hindered amine light stabilizer, a middle layer thermoplastic polyurethane layer containing a double crosslinking network, and an inner layer glass fiber reinforced polycarbonate layer. Through material modification, uniform distribution and dense combination of the materials in each layer are realized, the impact resistance and weather resistance of the battery shell are significantly improved, and excellent combination of the interface is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery casing manufacturing technology, and relates to a high-impact PC-elastomer composite battery casing and its preparation method. Background Technology

[0002] The battery casing is a crucial component of a battery system, responsible for providing physical protection, structural support, and electrical insulation for the battery cells. In applications such as electric vehicles, portable electronic devices, and energy storage systems, the battery casing not only needs high strength and impact resistance to withstand external mechanical shocks, but also requires a certain level of heat resistance and chemical corrosion resistance to ensure safe use in various harsh environments. Furthermore, the weight of the battery casing is also a key consideration; lightweight design helps improve the energy efficiency and range of the device.

[0003] Traditional battery casing materials are typically made of metals (such as aluminum alloys and stainless steel) or plastics (such as polycarbonate and polypropylene). Metals are widely used due to their excellent mechanical strength and heat resistance, but their higher density increases the overall weight of the battery system. On the other hand, plastics have become an alternative due to their lightweight nature and flexibility in molding and processing, but their mechanical properties and heat resistance are generally inferior to metals. In recent years, composite materials have gradually become a research hotspot in order to balance lightweight and high performance, especially glass fiber reinforced plastics and carbon fiber reinforced composites, which significantly reduce weight while maintaining excellent mechanical properties.

[0004] Despite advancements in material properties and processing techniques, existing technologies still have several shortcomings. Traditional metal casings are heavy and prone to chemical reactions in corrosive environments, affecting their lifespan. Plastic casings, on the other hand, suffer from poor heat resistance and aging resistance, potentially leading to deformation and cracking over long-term use. Furthermore, while composite materials have shown improved performance, their high production costs and manufacturing complexity limit their application in large-scale industrial production. Particularly in the electric vehicle sector, there is an urgent need to develop new battery casing materials that are not only lightweight and impact-resistant but also possess excellent weather resistance and cost-effectiveness to meet growing market demands and stringent performance requirements. Summary of the Invention

[0005] The purpose of this invention is to provide a high-impact PC-elastomer composite battery casing and its preparation method, providing a battery casing with high impact resistance, weather resistance and lightweight characteristics.

[0006] The objective of this invention can be achieved through the following technical solutions: A high-impact PC-elastomer composite battery casing includes an outer layer, a middle layer, and an inner layer stacked sequentially. The outer layer is a polycarbonate layer grafted with hindered amine light stabilizer; The intermediate layer is a thermoplastic polyurethane layer containing double cross-linked network molecular chain segments; The inner layer is a glass fiber reinforced polycarbonate layer, wherein the glass fiber is treated with a bifunctional coupling agent containing isocyanate groups and siloxane groups, and the polycarbonate resin is grafted and modified with maleic anhydride or glycidyl groups.

[0007] As a preferred embodiment of the present invention, the hindered amine light stabilizer is grafted onto the end groups of the polycarbonate molecular chain via an esterification reaction.

[0008] As a preferred embodiment of the present invention, the dual-crosslinked network includes: Polyurethane hard segments formed by chain extension of diphenylmethane diisocyanate and 1,4-butanediol; Reversible crosslinking of furan-modified polycaprolactone diol and bismaleimide via Diels-Alder reaction.

[0009] As a preferred embodiment of the present invention, the bifunctional coupling agent is propyltriethoxysilane isocyanate.

[0010] Furthermore, the method for preparing the high-impact PC-elastomer composite battery casing includes the following steps: (1) The modified glass fiber and grafted polycarbonate resin were blended and injection molded into the inner layer; (2) The double-network thermoplastic polyurethane granules are injection molded onto the inner surface of the inner layer obtained in step (1) to form an intermediate layer; (3) The hindered amine light stabilizer HALS grafted polycarbonate is injection molded onto the surface of the intermediate layer obtained in step (2) as the outer layer. The molding temperature is controlled at 230-250℃ and the interlayer bonding pressure is 80-120 MPa to obtain the outer layer.

[0011] In this application, the outer layer of carboxyl-terminated polycarbonate undergoes an esterification reaction with the hydroxyl groups of HALS under the catalysis of a condensing agent. The chemical bonding binds HALS to the ends of the PC molecular chain, preventing the migration and precipitation of small molecules. The middle layer of double crosslinking includes polyurethane hard segment covalent crosslinking to provide rigid support and Diels-Alder reversible crosslinking to absorb impact. In the inner layer, the -NCO groups of the modified glass fiber react with the anhydride or epoxy groups of the grafted polycarbonate resin to improve the dispersion and bonding of the glass fiber and the resin.

[0012] As a preferred technical solution of the present invention, the modified glass fiber in step (1) is prepared by: immersing the glass fiber in an ethanol solution containing 1-5 wt% propyltriethoxysilane isocyanate and drying and curing it at 110-130°C. The grafted polycarbonate resin is prepared by: melting and grafting polycarbonate resin, maleic anhydride or glycidyl methacrylate and free radical initiator benzoyl peroxide. The mass ratio of the modified glass fiber to the grafted polycarbonate resin is 0.2-0.35:1.

[0013] As a preferred technical solution of the present invention, the method for preparing the intermediate layer in step (2) includes the following steps: A1. Polycaprolactone diol and diphenylmethane diisocyanate were heated to 75-85℃ and stirred for 1-3 h under nitrogen protection. Then 1,4-butanediol and dibutyltin dilaurate were added and the reaction was continued for 1-2 h to obtain the terminal isocyanate prepolymer. A2. Furan-modified polycaprolactone diol and bismaleimide are melt-blended at 110-130℃ for 5-15 min, and the furan ring and maleimide group undergo cycloaddition to form a dynamic crosslinked premix. A3. The prepolymer obtained in step A1 and the dynamic crosslinking premix obtained in step A2 are blended at 120-130℃ for 5-10 minutes to obtain the final product.

[0014] As a preferred technical solution of the present invention, the preparation method of furan-modified polycaprolactone diol in step A2 is as follows: polycaprolactone diol and furanaldehyde are subjected to an esterification reaction under the catalysis of p-toluenesulfonic acid.

[0015] As a preferred technical solution of the present invention, the preparation method of the outer layer in step (3) is as follows: the carboxyl-terminated polycarbonate, the hindered amine light stabilizer HALS, and the condensing agent N,N'-dicyclohexylcarbonimide are subjected to an esterification reaction at 160-190℃ to obtain the outer layer.

[0016] As a preferred embodiment of the present invention, the thickness ratio of the inner layer, the middle layer and the outer layer is 30-50:30-40:15-25.

[0017] The beneficial effects of this invention are: (1) The present invention improves the impact resistance of the battery casing through a three-layer structure. The outer layer uses PC as the initial impact dispersion. The middle layer absorbs the impact energy. The middle layer double cross-linked network contains polyurethane hard segments and a cross-linked structure of furan-polycaprolactone diol and bismaleimide. During impact, the polyurethane hard segments provide basic mechanical strength and toughness. At the same time, the Diels-Alder reaction dissipates the impact energy through chain segment slippage, further improving the impact resistance. The inner layer provides a rigid skeleton for the battery casing by adding modified glass fiber to resist local deformation during impact.

[0018] (2) The hindered amine grafted to the PC end groups of the outer layer of the present invention contains secondary amine groups, which can bind to the terminal isocyanate groups of the intermediate double crosslinked TPU; at the same time, the hydroxyl groups of the TPU soft segment (polycaprolactone diol) form hydrogen bonds with the carbonate groups of the outer PC, forming a double interface bond. The terminal isocyanate groups of the intermediate TPU can undergo covalent reactions with the carboxyl or epoxy groups of the PC grafted with maleic anhydride or glycidyl groups of the inner layer to generate amide bonds or epoxy amine bonds; in addition, after the glass fiber surface is treated with propyltriethoxysilane, the siloxane is hydrolyzed to generate silanol, which condenses with the hydroxyl groups of PC to form siloxane bonds, further enhancing the interface bond.

[0019] (3) The outer PC layer of this invention is grafted with hindered amine light stabilizers via esterification. The piperidine ring in the HALS molecular chain can capture UV-induced free radicals and inhibit the photo-oxidative degradation of PC. At the same time, HALS is chemically bonded to the end groups of the PC molecular chain, avoiding the migration and precipitation problems of traditional additive HALS. The inner layer is reinforced with modified glass fiber, which reduces the amount of material used while ensuring rigidity and reduces the density compared to traditional metal shells. Detailed Implementation

[0020] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with embodiments, is provided below.

[0021] Example 1 A high-impact PC-elastomer composite battery casing, comprising a three-layer composite structure: (a) Outer layer: Polycarbonate layer with end-group grafted hindered amine light stabilizer; (b) Intermediate layer: a thermoplastic polyurethane layer containing a double cross-linked network; (c) Inner layer: glass fiber reinforced polycarbonate layer, wherein the glass fiber is treated with a bifunctional coupling agent containing isocyanate groups and siloxane groups, and the polycarbonate resin is grafted with maleic anhydride.

[0022] The hindered amine light stabilizer is grafted onto the end groups of the polycarbonate molecular chain via an esterification reaction.

[0023] The dual-crosslink network includes: Polyurethane hard segments formed by chain extension of diphenylmethane diisocyanate and 1,4-butanediol; Reversible crosslinking of furan-modified polycaprolactone diol and bismaleimide via Diels-Alder reaction.

[0024] The bifunctional coupling agent is propyltriethoxysilane isocyanate.

[0025] The method for preparing a high-impact PC-elastomer composite battery casing includes the following steps: (1) The modified glass fiber and grafted polycarbonate resin were blended and injection molded into the inner layer; (2) The double-network thermoplastic polyurethane granules are injection molded onto the inner surface of the inner layer obtained in step (1) to form an intermediate layer; (3) The hindered amine light stabilizer grafted polycarbonate is injection molded onto the surface of the intermediate layer obtained in step (2) as the outer layer. The molding temperature is controlled at 240℃ and the interlayer bonding pressure is 100 MPa to obtain the outer layer.

[0026] The modified glass fiber in step (1) is prepared by impregnating the glass fiber in an ethanol solution containing 3 wt% propyltriethoxysilane isocyanate and drying and curing it at 120°C. The grafted polycarbonate resin is prepared by: melting and grafting polycarbonate resin, maleic anhydride, and free radical initiator benzoyl peroxide. The mass ratio of the modified glass fiber to the grafted polycarbonate resin is 0.3:1.

[0027] The preparation method of the dual-network thermoplastic polyurethane granules in step (2) includes the following steps: A1. 100 parts by weight of polycaprolactone diol and 38 parts by weight of diphenylmethane diisocyanate were heated to 80°C and stirred for 2 h under nitrogen protection. Then 10 parts by weight of 1,4-butanediol and 0.05 parts by weight of dibutyltin dilaurate were added, and the reaction was continued for 1.5 h to obtain the isocyanate-terminated prepolymer. A2. 25 parts by weight of furan-modified polycaprolactone diol and 6 parts by weight of bismaleimide are melt-blended at 120°C for 10 min to form a dynamic cross-linked premix. A3. The prepolymer obtained in step A1 and the dynamic crosslinking premix obtained in step A2 are blended at 125°C for 7 minutes, and then granulated after cooling.

[0028] The preparation method of furan-modified polycaprolactone diol in step A2 is as follows: 100 parts by weight of polycaprolactone diol and 16 parts by weight of furanaldehyde are subjected to an esterification reaction in the presence of 0.6 parts by weight of p-toluenesulfonic acid catalyst.

[0029] The outer layer in step (3) is prepared by esterification of 100 parts by weight of carboxyl-terminated polycarbonate, 10 parts by weight of hindered amine light stabilizer HALS, 15 parts by weight of condensing agent N,N'-dicyclohexylcarbonimide, and 0.8 parts by weight of catalyst 4-dimethylaminopyridine at 170°C.

[0030] The thickness ratio of the inner layer, middle layer, and outer layer is 40:35:20; the thickness of the battery casing is 2mm.

[0031] Example 2 A high-impact PC-elastomer composite battery casing, comprising a three-layer composite structure: (a) Outer layer: Polycarbonate layer with end-group grafted hindered amine light stabilizer; (b) Intermediate layer: a thermoplastic polyurethane layer containing a double cross-linked network; (c) Inner layer: Glass fiber reinforced polycarbonate layer, wherein the glass fiber is treated with a bifunctional coupling agent containing isocyanate and siloxane groups, and the polycarbonate resin is grafted with glycidyl groups.

[0032] The hindered amine light stabilizer is grafted onto the end groups of the polycarbonate molecular chain via an esterification reaction.

[0033] The dual-crosslink network includes: Polyurethane hard segments formed by chain extension of diphenylmethane diisocyanate and 1,4-butanediol; Reversible crosslinking of furan-modified polycaprolactone diol and bismaleimide via Diels-Alder reaction.

[0034] The bifunctional coupling agent is propyltriethoxysilane isocyanate.

[0035] The method for preparing a high-impact PC-elastomer composite battery casing includes the following steps: (1) The modified glass fiber and grafted polycarbonate resin were blended and injection molded into the inner layer; (2) The double-network thermoplastic polyurethane granules are injection molded onto the inner surface of the inner layer obtained in step (1) to form an intermediate layer; (3) The hindered amine light stabilizer grafted polycarbonate is injection molded onto the surface of the intermediate layer obtained in step (2) as the outer layer. The molding temperature is controlled at 230°C and the interlayer bonding pressure is 80 MPa to obtain the outer layer.

[0036] The modified glass fiber in step (1) is prepared by immersing the glass fiber in an ethanol solution containing 1 wt% propyltriethoxysilane isocyanate and drying and curing it at 110°C. The grafted polycarbonate resin is prepared by: melting and grafting polycarbonate resin, glycidyl methacrylate, and benzoyl peroxide free radical initiator. The mass ratio of the modified glass fiber to the grafted polycarbonate resin is 0.2:1.

[0037] The preparation method of the dual-network thermoplastic polyurethane granules in step (2) includes the following steps: A1. 100 parts by weight of polycaprolactone diol and 35 parts by weight of diphenylmethane diisocyanate were heated to 75°C and stirred for 1 h under nitrogen protection. Then 8 parts by weight of 1,4-butanediol and 0.02 parts by weight of dibutyltin dilaurate were added, and the reaction was continued for 1 h to obtain the isocyanate-terminated prepolymer. A2. 20 parts by weight of furan-modified polycaprolactone diol and 5 parts by weight of bismaleimide are melt-blended at 110°C for 5 min to form a dynamic cross-linked premix. A3. The prepolymer obtained in step A1 and the dynamic crosslinking premix obtained in step A2 are mixed at 120℃ for 5 minutes, and then granulated after cooling.

[0038] The preparation method of furan-modified polycaprolactone diol in step A2 is as follows: 90 parts by weight of polycaprolactone diol and 14 parts by weight of furanaldehyde are esterified in the presence of 0.5 parts by weight of p-toluenesulfonic acid catalyst.

[0039] The outer layer in step (3) is prepared by esterification of 90 parts by weight of carboxyl-terminated polycarbonate, 8 parts by weight of hindered amine light stabilizer HALS, 12 parts by weight of condensing agent N,N'-dicyclohexylcarbonimide, and 0.5 parts by weight of catalyst 4-dimethylaminopyridine at 160°C.

[0040] The thickness ratio of the inner layer, middle layer, and outer layer is 30:30:15; the thickness of the battery casing is 2mm.

[0041] Example 3 A high-impact PC-elastomer composite battery casing, comprising a three-layer composite structure: (a) Outer layer: Polycarbonate layer with end-group grafted hindered amine light stabilizer; (b) Intermediate layer: a thermoplastic polyurethane layer containing a double cross-linked network; (c) Inner layer: glass fiber reinforced polycarbonate layer, wherein the glass fiber is treated with a bifunctional coupling agent containing isocyanate groups and siloxane groups, and the polycarbonate resin is grafted with maleic anhydride.

[0042] The hindered amine light stabilizer is grafted onto the end groups of the polycarbonate molecular chain via an esterification reaction.

[0043] The dual-crosslink network includes: Polyurethane hard segments formed by chain extension of diphenylmethane diisocyanate and 1,4-butanediol; Reversible crosslinking of furan-modified polycaprolactone diol and bismaleimide via Diels-Alder reaction.

[0044] The bifunctional coupling agent is propyltriethoxysilane isocyanate.

[0045] The method for preparing a high-impact PC-elastomer composite battery casing includes the following steps: (1) The modified glass fiber and grafted polycarbonate resin were blended and injection molded into the inner layer; (2) The double-network thermoplastic polyurethane granules are injection molded onto the inner surface of the inner layer obtained in step (1) to form an intermediate layer; (3) The hindered amine light stabilizer grafted polycarbonate is injection molded onto the surface of the intermediate layer obtained in step (2) as the outer layer. The molding temperature is controlled at 250°C and the interlayer bonding pressure is 120 MPa to obtain the outer layer.

[0046] The modified glass fiber in step (1) is prepared by immersing the glass fiber in an ethanol solution containing 5 wt% propyltriethoxysilane isocyanate and drying and curing it at 130°C. The grafted polycarbonate resin is prepared by: melting and grafting polycarbonate resin, maleic anhydride or glycidyl methacrylate and free radical initiator benzoyl peroxide. The mass ratio of the modified glass fiber to the grafted polycarbonate resin is 0.35:1.

[0047] The preparation method of the dual-network thermoplastic polyurethane granules in step (2) includes the following steps: A1. 100 parts by weight of polycaprolactone diol and 40 parts by weight of diphenylmethane diisocyanate were heated to 85°C and stirred for 3 h under nitrogen protection. Then 12 parts by weight of 1,4-butanediol and 0.08 parts by weight of dibutyltin dilaurate were added, and the reaction was continued for 2 h to obtain the isocyanate-terminated prepolymer. A2. 30 parts by weight of furan-modified polycaprolactone diol and 8 parts by weight of bismaleimide are melt-blended at 130°C for 15 min to form a dynamic cross-linked premix. A3. The prepolymer obtained in step A1 and the dynamic crosslinking premix obtained in step A2 are blended at 130°C for 10 min, and then cooled and granulated to obtain the final product.

[0048] The preparation method of furan-modified polycaprolactone diol in step A2 is as follows: 100 parts by weight of polycaprolactone diol and 18 parts by weight of furanaldehyde are esterified in the presence of 0.8 parts by weight of p-toluenesulfonic acid catalyst.

[0049] The outer layer in step (3) is prepared by esterification of 100 parts by weight of carboxyl-terminated polycarbonate, 12 parts by weight of hindered amine light stabilizer HALS, 18 parts by weight of condensing agent N,N'-dicyclohexylcarbonimide, and 1.0 parts by weight of catalyst 4-dimethylaminopyridine at 190°C.

[0050] The thickness ratio of the inner layer, middle layer, and outer layer is 50:40:25; the thickness of the battery casing is 2mm.

[0051] Comparative Example 1 Based on Example 1, the modification treatment of glass fiber is omitted, and the rest is the same as in Example 1.

[0052] Comparative Example 2 Based on Example 1, the grafting modification treatment of the inner polycarbonate resin is omitted, and the rest is consistent with Example 1.

[0053] Comparative Example 3 Based on Example 1, the intermediate layer uses untreated thermoplastic polyurethane granules, while the rest remains the same as in Example 1.

[0054] Comparative Example 4 Based on Example 1, the hindered amine light stabilizer HALS was directly mixed with polycarbonate resin as the outer layer, and the rest remained the same as in Example 1.

[0055] Performance testing: Impact resistance: The impact resistance of flat, rigid plastic specimens was determined according to ASTM D5628 standard using a 5kg steel ball, starting from a height of 1m, with the height gradually increased by 0.2m until the specimen broke. Interlaminar peel strength: The interlaminar glass strength was tested according to ASTM D1876 standard (T-type peel, tensile rate 100 mm / min). Aging resistance: The impact strength retention rate was tested after aging according to ISO 4892-3 standard (UVB-313 lamp, 0.55 W / m2, 60℃); The test results above show that unmodified glass fiber in Comparative Example 1 may lead to interfacial debonding, resulting in a decrease in impact energy absorption rate; the inner polycarbonate resin in Comparative Example 2 is grafted, and its peel strength also decreases significantly; Comparative Example 3 shows the largest decrease in impact height, indicating that the double cross-linking of the intermediate layer has an absorption and buffering function for impact energy; and the direct mixing of hindered amine light stabilizer HALS in Comparative Example 4 leads to a significant decrease in anti-aging performance.

[0056] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any indirect modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for preparing a high-impact PC-elastomer composite battery casing, characterized in that: Includes the following steps: (1) The modified glass fiber and grafted polycarbonate resin were blended and injection molded into the inner layer; (2) Injection molding of double-network thermoplastic polyurethane granules onto the surface of the inner layer obtained in step (1) to form an intermediate layer; (3) The hindered amine light stabilizer grafted polycarbonate is injection molded onto the surface of the intermediate layer obtained in step (2) as the outer layer. The molding temperature is controlled at 230-250℃ and the interlayer bonding pressure is 80-120 MPa to obtain the outer layer. The modified glass fiber in step (1) is prepared by immersing the glass fiber in an ethanol solution containing 1-5 wt% propyltriethoxysilane isocyanate and drying and curing it at 110-130℃. The grafted polycarbonate resin is prepared by: melting and grafting polycarbonate resin, maleic anhydride or glycidyl methacrylate and free radical initiator benzoyl peroxide. The mass ratio of the modified glass fiber to the grafted polycarbonate resin is 0.2-0.35:1; The preparation method of the dual-network thermoplastic polyurethane granules in step (2) includes the following steps: A1. Polycaprolactone diol and diphenylmethane diisocyanate were heated to 75-85℃ and stirred for 1-3 h under nitrogen protection. Then 1,4-butanediol and dibutyltin dilaurate were added and the reaction was continued for 1-2 h to obtain the terminal isocyanate prepolymer. A2. Furan-modified polycaprolactone diol and bismaleimide are melt-blended at 110-130℃ for 5-15 min to form a dynamic cross-linked premix. A3. The prepolymer obtained in step A1 is blended with the dynamic crosslinking premix obtained in step A2 at 120-130℃ for 5-10 min to obtain the product. The outer layer in step (3) is prepared by esterification of carboxyl-terminated polycarbonate, hydroxyl-containing hindered amine light stabilizer HALS, and condensing agent N,N'-dicyclohexylcarbonimide at 160-190℃.

2. The method for preparing a high-impact PC-elastomer composite battery casing according to claim 1, characterized in that: The preparation method of furan-modified polycaprolactone diol in step A2 is as follows: polycaprolactone diol and furanaldehyde are reacted under the catalysis of p-toluenesulfonic acid.

3. The method for preparing a high-impact PC-elastomer composite battery casing according to claim 1, characterized in that: The thickness ratio of the inner layer, middle layer, and outer layer is 30-50:30-40:15-25.

Citation Information

Patent Citations

  • High-weather-resistance ABS (acrylonitrile butadiene styrene) composite decorating part for automobile and preparation method thereof

    CN115449035A

  • Thermoplastic multilayer articles, methods of manufacture, and uses thereof

    US20220203657A1